The world we could win : administering global governance - Fraser-Moleketi, Geraldine (International Institute of Administrative Sciences monographs, 2005)
Containing six essays, this volume looks thematically at different elements or facets of Global Governance and the issues that arise. It deals with some regional perspectives on Global Governance. It aims to raise our eyes beyond the known world in public administration and also looks at the unit of analysis.